Neuronal Subset-Specific Migration and Axonal Wiring Mechanisms in the Developing Midbrain Dopamine System - Sara Brignani; R. J. Pasterkamp (Frontiers Media S.A., 2017)
The midbrain dopamine (mDA) system is involved in the control of cognitive and motor behaviors, and is associated with several psychiatric and neurodegenerative diseases. mDA neurons receive diverse afferent inputs and establish efferent connections with many brain areas. Recent studies have unveiled a high level of molecular and cellular heterogeneity within the mDA system with specific subsets of mDA neurons displaying select molecular profiles and connectivity patterns. During mDA neuron development, molecular differences between mDA neuron subsets allow the establishment of subset-specific afferent and efferent connections and functional roles. In this review, we summarize and discuss recent work defining novel mDA neuron subsets based on specific molecular signatures. Then, molecular cues are highlighted that control mDA neuron migration during embryonic development and that facilitate the formation of selective patterns of efferent connections. The review focuses largely on studies that show differences in these mechanisms between different subsets of mDA neurons and for which in vivo data is available, and is concluded by a section that discusses open questions and provides directions for further research.